Influence of Internal Service Quality on Loyalty Medited By Employee Satisfaction - Dharmawan, Denny; Ilmi, Zainal; Wijaya, Adi (Green Publisher Indonesia, 2022)
The purpose of this study was to analyze and prove the influence of the influence of internal service quality on loyalty mediated by job satisfaction of employees at pt. Mahakam Gate of the King of Oil and Gas (Persero) in Kutai Kartanegara Regency. This study used 40 respondents and this study used a survey method with a sample of employees at PT. Mahakam Gate Raja Migas (Perseroda) in Kutai Kartanegara Regency with census sampling technique . Respondents were only interviewed once when they met. Data from the respondents were then tabulated and tested using statistical methods. Data were collected using a questionnaire research tool. Based on the results of the analysis and discussion, it can be concluded that the quality of Internal Services has no effect on employee job satisfaction, meaning that the previously formulated hypothesis is rejected, so that if the quality of Internal Services has increased, it will not have an impact on increasing job satisfaction. The quality of Internal Services has no effect on employee loyalty, meaning that the previously formulated hypothesis is rejected, so that if the quality of Internal Services has increased, it will not have an impact on increasing loyalty. Loyalty has a positive influence on employee job satisfaction, meaning that the previously formulated hypothesis is accepted, so that if Loyalty increases, then job satisfaction will also increase, in line with the increase in Loyalty.